Earnings Management Activities: Discretionary Accruals And Real Activity Manipulation - Julia, Julia; Saputra, Darman; Hamsani, Hamsani (Integrated Journal of Business and Economics (IJBE), 2025)
This study examines earnings management practices using discretionary accruals and real activities manipulation in Indonesia’s property and real estate sector during 2022–2023, given the potential of such practices to mislead financial statement users in this rapidly growing industry. Employing a descriptive quantitative approach with secondary data, 72 firm-year samples were selected through purposive sampling. The findings reveal clear indications of earnings management via both accruals and real activities, with a significant difference observed between the two methods. These results extend Agency Theory by highlighting dual strategies used in post-pandemic contexts and underscore the need for regulators (OJK, IDX) to strengthen disclosure and oversight policies. For practitioners, the findings emphasize the importance of ethical reporting and improved internal controls to enhance financial transparency and investor trust.